Unearthing Key Themes in Cryptoeconomics: A Novel Text-Mining Study with Orange - Satibi, Iswanda (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2025)
Cryptoeconomics, an interdisciplinary intersection of cryptography, economics, and decentralized systems, has matured well past its speculative cryptocurrency roots. This study contextualizes cryptoeconomics in history by looking at topic trends over time. Arranging topic prevalence over time according to the dates of key events, provides further insights into external drivers that correlate with research priorities. Leveraging commonly accepted bibliometric resources, we conduct a mixed-method systematic literature review of 585 peer-reviewed studies (2013–2024) and a series of quantitative analyses using Document-Term Matrices (DTM), with TF-IDF weighting and Latent Dirichlet Allocation (LDA) in Orange—supplemented with LDAVis in order to render structural insights as an interactive dimension—aimed to chart the intellectual landscape of cryptoeconomics. Basic text preprocessing steps resulted in 4,638 nonnaive terms from 72,695 original ones, keeping the vocabulary within the specific domain. Given the 10-topic LDA model, we are able to highlight three major results: (1) finance still plays an overwhelming role with great focus on the valuation, volatility and regulation of cryptocurrency assets; (2) governance and sustainability have become two major clusters showing that clear institutional design and ecological awareness in the use of blockchain technologies will be crucial moving forward; (3) technical-contextual pairing, with niche words like “felsic” signaling the move on finance’s potential spillover effects across resource management, supply chains, and a myriad of socio-technical ecosystems. These results on the one hand show that cryptoeconomics is at a crossroad, moving from the narrow public debate around cryptocurrencies themselves to become more a wider discussion charting a ray of financial technology, energy consumption, security and equitable governance. Applying automated topic modeling to qualitative interpretation strengthens the holistic understanding of how cryptoeconomics interacts with real-world problems. This study shines a light in potential inter disciplinary gaps and emergent themes in decentralized architecture, thereby providing a consolidated basis for a forthcoming empirical study, regulatory representatives, and technological implementations that promote alignment between decentralized architecture and human and environmental values.